Alternating‐Current MXene Polymer Light‐Emitting Diodes. (17th June 2020) - Lee, Seokyeong; Kim, Eui Hyuk; Yu, Seunggun; Kim, Hyerim; Park, Chanho; Park, Tae Hyun; Han, Hyowon; Lee, Seung Won; Baek, Soyeon; Jin, Wookyoung; Koo, Chong Min; Park, Cheolmin
Abstract: MXenes (Ti3 C2 ) are 2D transition‐metal carbides and carbonitrides with high conductivity and optical transparency. However, transparent MXene electrodes suitable for polymer light‐emitting diodes (PLEDs) have rarely been demonstrated. With the discovery of the excellent electrical stability of MXene under an alternating current (AC), herein, PLEDs that employ MXene electrodes and exhibit high performance under AC operation (AC MXene PLEDs) are presented. The PLED exhibits a turn‐on voltage, current efficiency, and brightness of 2.1 V, 7 cd A −1, and 12 547 cd m −2, respectively, when operated under AC with a frequency of 1 kHz. The results indicate that the undesirable electric breakdown associated with heat arising from the poor interface of the MXene with a hole transport layer in the direct‐current mode is efficiently suppressed by the transient injection of carriers accompanied by the alternating change of the electric polarity under the AC, giving rise to reliable light emission with a high efficiency. The solution‐processable MXene electrode can be readily fabricated on a flexible polymer substrate, allowing for the development of a mechanically flexible AC MXene PLED with a higher performance than flexible PLEDs employing solution‐processed nanomaterial‐based electrodes such as carbon nanotubes, reduced graphene oxide, and Ag nanowires. Abstract : Alternating‐current operation of a polymer light emitting diode (PLED) with a MXene electrode consisting of 2D flakes is critical for ensuring a high performance, which is superior to that of previously reported flexible PLEDs with solution‐processed nanomaterial‐based electrodes such as C nanotubes, reduced graphene oxide, and Ag nanowires, making it a promising candidate for the development of next‐generation transparent displays.